PERUBAHAN SOSIAL MASYARAKAT PADA ERA MULTIMEDIA DI KELURAHAN WINANGUN I KECAMATAN MALALAYANG - Muaja, Lively Jefta; Kawung, Eveline J. R.; Goni, Shirley Y. V. I. (HOLISTIK, Journal Of Social and Culture, 2018)
The development of multimedia currently has also contributed to the provision of social media community especially in the communication needs users, as well as in supporting the process of learning how to teach at education institutions. The development of technology computer hardware and software user computer application in activities for working people, that is why every single human being out there always in charge in trying to adapt to the various communications technology to facilitate the multimedia world abreast of developments in technology.In developmentally where multimedia may make it easier for human beings in do many things, not of mean things which make it always have a positive impact for the environment the community, there are the negative impact of what it felt like start of yourself as user and the impact of that exert influence over the environment.Technological progress communication especially the use of social media apparently had an impact that diverse in society in general such as changes on how to work, behavior and social life and improve thought behavior more developed and negative impact on notice some people of technology in Kelurahan Winangun Satu Kecamatan Malalayang Kota Manado.Technology development communication have an impact on the occurrence of a change in society as pattern behavior each individual start less sociable a fellow member of the communities of which each individual sometimes busy with itself because affected by the presence of the development in the world multimedia. Keywords: multimedia, communication, social